Are CFOs’ Trades More Informative Than CEOs’ Trades? - Wang, Weimin; Shin, Yong-Chul; Francis, Bill B. (Journal of Financial and Quantitative Analysis, 2012)
Abstract We investigate whether trades made by chief financial officers (CFOs) reveal more information about future stock returns than those by chief executive officers (CEOs). We find that CFOs earn statistically and economically higher abnormal returns following their purchases of company shares than CEOs. During 1992–2002, CFOs earned an average 12-month excess return that is 5% higher than that by CEOs. The superior performance by CFOs occurs notwithstanding controls for risk factors and persists even after their trades are publicly disclosed. Further analysis shows that CFO purchases are associated with more positive future earnings surprises than CEO purchases, suggesting that CFOs incorporate better information about future earnings.